Pengembangan Produk Baru dengan menggunakan Means-End Chain Theory : Kasus Water+ - Aldinata Windharta; Andre Christian Efendy; Daniel Christian; M. Rashid Damahuri (Universitas Prasetiya Mulya, 2019)
The author aims to find out about urban people needs in bottled mineral water. The author uses the Means-End-Chain method which is commonly used to find what attributes are needed by consumers of a product or service. This research uses qualitative methods with in-depth interviews to answer the question of what content is most expected of urban communities in bottled mineral water. There are three factors that we examine, namely attributes, consequences, and values. By understanding the means end chain from our sample, we hope that related party can develop a product from our research result.